A Case Series on Cholera Amongst Migrant Workers in a Semi-Urban Area of Western Maharashtra - Mukesh Bawa; Pawan Giram; Sachin Deorukhkar; Atul Desale; Harshal Pandve; Pandurang Thatkar (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Cholera remains a significant public health challenge, particularly in areas lacking adequate water supply and sanitation infrastructure. This case series describes six cases of Vibrio cholerae confirmed infection in Mahalunge Ingale, Khed, Maharashtra, characterized by acute watery diarrhea, vomiting, and varying degrees of dehydration. All cases were confirmed to be Vibrio cholerae O1, Ogawa serotype strain. Despite prompt treatment with aggressive intravenous fluid resuscitation and empirical antibiotic therapy (doxycycline), outcomes varied: four patients showed clinical improvement and were discharged, one patient succumbed to multiorgan dysfunction syndrome, and another left against medical advice. Acute kidney injury emerged as a serious complication, emphasizing the critical role of early and adequate fluid management in addressing cholera-associated complications. The index case of confirmed cholera was admitted to Tertiary Teaching Care Hospital, Pimpri, Pune on 16/05/2024 from Mahalunge Ingale, Dist. Pune, Western Maharashtra. This is a case series of 6 cases coming from the same location from the period of 16/05/2024 to 02/06/2024. This study underscores the imperative of timely medical intervention and robust public health interventions to effectively manage cholera outbreaks.